Effects of Sweeteners on the Gut Microbiota: A Review of Experimental Studies and Clinical Trials. (5th February 2019) - Ruiz-Ojeda, Francisco Javier; Plaza-Díaz, Julio; Sáez-Lara, Maria Jose; Gil, Angel
ABSTRACT: The consumption of sugar-free foods is growing because of their low-calorie content and the health concerns about products with high sugar content. Sweeteners that are frequently several hundred thousand times sweeter than sucrose are being consumed as sugar substitutes. Although nonnutritive sweeteners (NNSs) are considered safe and well tolerated, their effects on glucose intolerance, the activation of sweet taste receptors, and alterations to the composition of the intestinal microbiota are controversial. This review critically discusses the evidence supporting the effects of NNSs, both synthetic sweeteners (acesulfame K, aspartame, cyclamate, saccharin, neotame, advantame, and sucralose) and natural sweeteners (NSs; thaumatin, steviol glucosides, monellin, neohesperidin dihydrochalcone, and glycyrrhizin) and nutritive sweeteners (polyols or sugar alcohols) on the composition of microbiota in the human gut. So far, only saccharin and sucralose (NNSs) and stevia (NS) change the composition of the gut microbiota. By definition, a prebiotic is a nondigestible food ingredient, but some polyols can be absorbed, at least partially, in the small intestine by passive diffusion: however, a number of them, such as isomalt, maltitol, lactitol, and xylitol, can reach the large bowel and increase the numbers of bifidobacteria in humans. Further research on the effects of sweeteners on the composition of the human gut microbiome is necessary.